Сучасні методи отримання ендофуллеренів заліза - Золотаренко, Ол. Д.; Аханова, Н. Е.; Золотаренко, Ан. Д.; Щур, Д. В.; Габдуллин, М. Т.; Уалханова, М.; Гаврилюк, Н. А.; Золотаренко, О. Д.; Чимбай, М. В.; Рудакова, О. П.; Мироненко, Т. В.; Загорулько, І. В.; et al. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2022)
The review examines experimental and theoretical works devoted to the description of modern methods for the preparation of iron endometal-fullerenes(EMF), as well as works that dispute such results due to the extremely low efficiency of the used methods. The paper also considers the advantages and disadvantages of synthesis, as well as the areas of possible application of synthesis products. It is shown that EMF is obtained mainly by two methods - arc discharge (plasma) and synthesis using ablation and implantation methods. Despite a very small number of works on iron-endometal-fullerenes, the group of authors managed to achieve some progress in their analysis. Thus, the fact of obtaining Fe-endometal-fullerenes with their isolation from a mixture of synthesis products was proved. In addition, the influence of the magnetic state of metal atoms on the stability of endohedral fullerenes was predicted, a relationship between the EMF output and the plasma temperature, as well as the chemical nature of the precursor of iron atoms, was established. In particular, it was established that with an increase in the atomic mass of the elements, the EMF output decreases exponentially. It was concluded that the magnetic properties of EMF make them perspective materials in the field of clinical diagnostics (for example, as contrast agents in MRI) and medicine (for magnetically controlled delivery of drugs directly to a diseased organ).